The influence of heat treatment on fracture surface morphology of the CuAlNi shape memory alloy. (July 2017) - Ivanić, Ivana; Kožuh, Stjepan; Kosel, Franc; Kosec, Borut; Anžel, Ivan; Bizjak, Milan; Gojić, Mirko
Abstract: The influence of different heat treatment temperatures on microstructural and mechanical properties of CuAlNi shape memory alloy was determined. The samples were investigated in as-cast state and heat treated state at three different temperatures (700 °C, 740 °C and 780 °C). The heat treatment was conducted at above mentioned temperatures for a very short period of time (2 min) followed by water quenching (WQ). The microstructures in all samples were martensitic, and only in the sample that was heat treated at 780 °C after tensile testing small particles of some other phase were observed. According to tensile testing measurement, some samples show better results, but insufficient elasticity for proceeding to cold plastic deformation processes. Fractographic analysis shows the intergranular type of fracture in the area of columnar grains and the transgranular type of fracture in the centre of the sample where the equiaxial grains appear. The microhardnesses of the samples were in the range between 239 and 305 HV10. Highlights: Microstructural and fracture analysis of CuAlNi SMA were analyzed. The influence of heat treatment on failure was determined. Fracture surface analysis showed intergranular and transgranular type of fracture. Elongation of the alloy was very low. Hardness of alloy was very high.